THE NATURE OF THE TAXES, FUNCTIONS AND PRINCIPLES OF TAXATION - Shulga, A. A. (Science and Transport Progress, 2007)
The criteria of tax payments differences from non-tax ones were determined, economic nature of charge was revealed, the essence of construction of the system of levy was formed.